Genome mining for the identification of secondary metabolites and alternative metabolic pathway modelling in Actinobacteria isolates (2017)
Actinobacteria produce a broad range of natural products (NP), encoded by biosynthetic gene clusters (BCG), with diverse biological activities and special pharmaceutical potential. However, a link between BGC prediction and metabolic pathway design has not been proposed. Genome mining of six Actinobacterial strains, isolated from Colombian environments, revealed 502 gene clusters encoding the biosynthesis of a variety of secondary metabolites, including PKS, NRPS, lanthipeptides and siderophores. Several optimization algorithms where then applied to find alternative, more thermodynamically efficient pathways for NP production. Despite the application of promising new tools, the results indicate that information in databases and modelling still requires improvement for future prediction and optimization of pathways regarding secondary metabolite production.